2016
DOI: 10.1021/acsomega.6b00080
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antibacterial Characterization of a Novel Fluorapatite Coating

Abstract: Peri-implantitis remains the major impediment to the long-term use of dental implants. With increasing concern over the growth in antibiotic resistance, there is considerable interest in the preparation of antimicrobial dental implant coatings that also induce osseointegration. One such potential coating material is fluorapatite (FA). The aim of this study was to relate the antibacterial effectiveness of FA coatings against pathogens implicated in peri-implantitis to the physicochemical properties of the coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…In a recent work of Alhilou et al . 28 , fluorapatite was investigated as a potential coating material for dental scaffolds/implants and it was demonstrated that it significantly reduces the viability of the adherent bacteria for all the bacterial strains tested (i.e. P .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work of Alhilou et al . 28 , fluorapatite was investigated as a potential coating material for dental scaffolds/implants and it was demonstrated that it significantly reduces the viability of the adherent bacteria for all the bacterial strains tested (i.e. P .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, implants made from titanium, stainless steel or cobalt-chrome alloys are frequently modified at the surface by bioceramics coatings that can be applied using different technologies, even though plasma spraying is the most popular and the Food and Drug Administration (FDA)-approved method [44]. In recent years, strategies based on the substitution of HAp by xF-HAp or FAp coatings has been proposed as effective strategies to decrease biofilm accumulation, to inhibit the demineralization process and to combat caries-related bacteria [45][46][47][48][49]. However, our results clearly indicate that such fluoride-therapy is more effective by supplying Fanions to the HAp coating from an external source (e.g.…”
Section: The Concentration Ofmentioning
confidence: 99%
“…If the drugs are inside the pores of the implant, the release rate will be lower, more controllable and the effect will last much longer [1012]. In the case of dental implants, such substances can lower the risks of peri-implantitis which is one of the leading causes for implant loss [1315].…”
Section: Background and Aimsmentioning
confidence: 99%